Technology Acceptance in AI-Mediated Communication: A Systematic Literature Review - Octavianus Bima Archa Wibowo; Fanny Octafiani; Irwansyah (Riviera Publishing, 2026)
This study investigates how AI is accepted within human communication, using the Technology Acceptance Model (TAM) as a guiding framework. While TAM has been widely applied in fields such as e-commerce and healthcare, its application in AI-mediated communication (AI-MC) remains limited. This research aims to synthesize current research, identify dominant variables, and examine conceptual and methodological gaps in TAM’s use within AI communication contexts. Specifically, it seeks to explore how TAM has been applied to explain user interaction with AI as a communicative agent, rather than merely as a functional tool. Methods: A Systematic Literature Review (SLR) was conducted using the PRISMA 2020, which ensured a transparent and structured review process. A total of 158 eligible articles published between 2015 and 2024 were analyzed using narrative synthesis and bibliometric mapping. The findings show that TAM’s core constructs perceived usefulness, perceived ease of use, and behavioral intention remain dominant but are often insufficient to explain the social, emotional, and ethical dimensions of AI as a communicative partner. The results highlight the growing importance of additional factors such as trust in AI, perceived agency, transparency, and emotional appropriateness. The review also reveals an over-reliance on quantitative methods, with limited integration of communication theory. Conclusion: As a result, a new conceptual framework is proposed that integrates TAM with human communication concepts, emphasizing co-constructed meaning, social presence, and ethical interaction. This study concludes that understanding AI acceptance in communication requires an interdisciplinary model that goes beyond technical functionality to consider human-AI relational dynamics.